Empirical Analysis of X-efficiency and Profitability Determinants of Commercial Banks in China - LI, LING (2018)
The paper firstly analyses the X-efficiency of 146 Chinese commercial banks over the period 2011-2017. In the result of the Stochastic Frontier Analysis(SFA), it shows a downward trend during this period and the average value is 0.6582. Then we focus on the 15 listed banks to find out the difference between the ownership and X-efficiency. The second step of the study to explore the determinants of performance in the Chinese banking sector using the fixed effects model (FEM), especially find out the effects of X-efficiency. From the aspects of bank-specific factors, operational efficiency, assets quality, liquidity and X-efficiency have the positive and significant impacts on the profitability. Furthermore, Chinese commercial banks are significantly affected by macroeconomic factors with GDP growth rate, unemployment rate and inflation rate, among them, the first two show the positive signs while the inflation rate adversely affects bank performance.